Gendered farm work, off-farm employment, and decision-making power: Quantitative evidence from Tajikistan - Lambrecht, Isabel B.; Mahrt, Kristi (International Food Policy Research Institute, 2022)
Globally, nearly half of all workers in rural areas work in agriculture (International Labour Organization 2020). Women are heavily involved in agricultural production, but often get assigned different roles and responsibilities compared to men (Doss 2018). In many contexts, women have less decision-making power than men regarding their households’ agricultural production or on how to spend agricultural income (FAO 2011). Yet, recent evidence suggests that a generalized assumption that women have no or little decision-making power in agriculture is misplaced and that there are also settings where joint decision-making between men and women is common (Akter et al. 2017; Maligalig et al. 2019). It therefore remains imperative to add new evidence on women’s and men’s roles and decision-making in agriculture – particularly from contexts that have not been extensively studied.